Accounting Treatment for Corporate Zakat in Indonesia - Andriani; Purwanti, Lilik (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
The implementation of zakat to companies is still a debate in Indonesia. Accounting standard for zakat fund is limited to the presentation of zakat funds reports only. This research raises the issue of comprehensive accounting standards for corporate zakat in Indonesia. The research was carried out through a qualitative approach with study documentation and literature review as the main method. Accounting treatment for corporate zakat in several countries will be discussed, i.e Malaysia and Bahrain. This research shows that corporate zakat can be recognized when it is approved by the General Meeting of Shareholders (GMS). Using profit as basis calculation of zakat is not considered. It is suggested that companies using assets as basis calculation for corporate zakat. Furthermore, Indonesian Islamic Banks (IBs) treat zakat as component of costs which deduct the company profit